Activation of the Unfolded Protein Response in Sporadic Inclusion-Body Myositis but Not in Hereditary GNE Inclusion-Body Myopathy. Issue 6 (June 2015) - Nogalska, Anna; D'Agostino, Carla; Engel, W. King; Cacciottolo, Mafalda; Asada, Shinichi; Mori, Kazutoshi; Askanas, Valerie
<x xml:space="preserve">Abstract</x> Abstract Muscle fibers in patients with sporadic inclusion-body myositis (s-IBM), the most common age-associated myopathy, are characterized by autophagic vacuoles and accumulation of ubiquitinated and congophilic multiprotein aggregates that contain amyloid-β and phosphorylated tau. Muscle fibers of autosomal-recessive hereditary inclusion-body myopathy caused by the GNE mutation (GNE-h-IBM) display similar pathologic features, except with less pronounced congophilia. Accumulation of unfolded/misfolded proteins inside the endoplasmic reticulum (ER) lumen leads to ER stress, which elicits the unfolded protein response (UPR) as a protective mechanism. Here we demonstrate for the first time that UPR is activated in s-IBM muscle biopsies, since there was 1) increased activating transcription factor 4 (ATF4) protein and increased mRNA of its target C/EBP homologous protein; 2) cleavage of the ATF6 and increased mRNA of its target glucose-regulated protein 78; and 3) an increase of the spliced form of X-box binding protein 1 and increased mRNA of ER degradation–enhancing α-mannosidase–like protein, target of heterodimer of cleaved ATF6 and spliced X-box binding protein 1. In contrast, we did not find similar evidence of the UPR induction in GNE-h-IBM patient muscle, suggesting that different intracellular mechanisms might lead to similar pathologic phenotypes. Interestingly, cultured GNE-h-IBM muscle fibers had a robust UPR response to experimental ER stress stimuli, suggesting that the GNE mutation per se is not responsible for the lack of UPR in GNE-h-IBM biopsied muscle.